2023
DOI: 10.3389/fpsyt.2023.1098292
|View full text |Cite
|
Sign up to set email alerts
|

The weaponization of medicine: Early psychosis in the Black community and the need for racially informed mental healthcare

Abstract: There is a notable disparity between the observed prevalence of schizophrenia-spectrum disorders in racialized persons in the United States and Canada and White individuals in these same countries, with Black people being diagnosed at higher rates than other groups. The consequences thereof bring a progression of lifelong punitive societal implications, including reduced opportunities, substandard care, increased contact with the legal system, and criminalization. Other psychological conditions do not show suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 111 publications
(185 reference statements)
0
19
0
Order By: Relevance
“…Second, there is a concern that Black individuals have been misdiagnosed (e.g., those with affective symptoms-mainly bipolar-who are diagnosed with schizophrenia; exaggeration of psychotic symptoms in poverty context; misinterpretation of cultural mistrust and racial discrimination experiences as paranoia symptoms) and medicated excessively (dosage and frequency) in cases of schizophrenia. 3,8 This echoes American studies that have shown that Black individuals were misdiagnosed and given more antipsychotic medication than people from other groups. Third, families consider court-ordered coercive measures for Black individuals diagnosed with psychosis to be generally abusive.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Second, there is a concern that Black individuals have been misdiagnosed (e.g., those with affective symptoms-mainly bipolar-who are diagnosed with schizophrenia; exaggeration of psychotic symptoms in poverty context; misinterpretation of cultural mistrust and racial discrimination experiences as paranoia symptoms) and medicated excessively (dosage and frequency) in cases of schizophrenia. 3,8 This echoes American studies that have shown that Black individuals were misdiagnosed and given more antipsychotic medication than people from other groups. Third, families consider court-ordered coercive measures for Black individuals diagnosed with psychosis to be generally abusive.…”
mentioning
confidence: 78%
“…This perception worries Black communities and fuels stigma among Black individuals regarding mental illnesses in general and psychosis in particular. 3 Over the past three decades in Canada significant disparities linked to psychosis within Black communities were observed. [4][5][6] Black individuals are at a higher prevalence of psychosis, experiencing involuntary admissions and treatments, having their first contact with healthcare institutions through emergency services in crisis situations, and are more likely to receive poor-quality care and demonstrate less adherence to medical treatments.…”
mentioning
confidence: 99%
“…Worry (rather than problem solving) may result in greater acute danger or unproductive outcomes (e.g., in the case of James, staring at the woman who crossed the street and making her more uncomfortable, perhaps prompting a confrontation or call to police). Unfortunately, the involvement of law enforcement rather than understanding or pathways to healthcare for Black Americans is staggering and results in more harm to the individual (Faber et al, 2023). The clinician employing a strategy based on an accurate conceptualization reduces the factor (worry) that puts the patient at increased risk by shifting engagement to productive behaviors (e.g., problem-solving, refocused activity).…”
Section: Treatment Implications Of the Casementioning
confidence: 99%
“…Accordingly, anxiety and mood disorders which have similarly implicated stress systems are also elevated in Black Americans (Berger & Sarnyai, 2015) and exhibit within-group increases as a function of higher race-based stress (Hudson et al, 2016). Black individuals experience higher rates of trauma and often meet criteria for PTSD at higher rates than White individuals, a well-established risk factor of psychosis (Faber et al, 2023). Elevations in stress hormones also result in changes to bodily functions, including hypertension, compromised immunity, etc.…”
Section: Treatment Implications Of the Casementioning
confidence: 99%
“…Cusack and colleagues [ 33 ] and, more recently, DeAngelis [ 34 ] have suggested that boys and men of color receive less comprehensive care, have less access to experienced providers, and are faced with fewer resources, while at the same time their mental health is challenged by racism. There continues to be a notable disparity between the prevalence of schizophrenia in people of color in the United States and Canada and their white counterparts in these same countries, with people of color receiving a higher diagnosis rate [ 35 ]. The overdiagnosis of Black and brown people is deeply rooted in the racial bias of practitioners and further illustrates the argument that service providers have not been trained to acknowledge or treat the trauma present within this group.…”
Section: The Restorative Integral Support (Ris) Modelmentioning
confidence: 99%